2017
DOI: 10.1186/s12931-017-0649-z
|View full text |Cite
|
Sign up to set email alerts
|

RIG-I overexpression decreases mortality of cigarette smoke exposed mice during influenza A virus infection

Abstract: BackgroundRetinoic acid-inducible gene I (RIG-I) is an important regulator of virus-induced antiviral interferons (IFNs) and proinflammatory cytokines which participate in clearing viral infections. Cigarette smoke (CS) exposure increases the frequency and severity of respiratory tract infections.MethodsWe generated a RIG-I transgenic (TG) mouse strain that expresses the RIG-I gene product under the control of the human lung specific surfactant protein C promoter. We compared the mortality and host immune resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 43 publications
(39 reference statements)
5
25
0
Order By: Relevance
“…12 Although in vitro and in vivo evidence suggests that RIG-I signaling is crucial for IFNs production to limit virus replication, particularly in the early stages of viral infection, long term overproduction of IFNs and cytokines can cause immunopathologic lung injury following acute IAV infection. [13][14][15][16][17] Thus, targeting RIG-I signaling to suppress RIG-I long-lasting hy- After 4 days, the number of plaques was then counted.…”
mentioning
confidence: 99%
“…12 Although in vitro and in vivo evidence suggests that RIG-I signaling is crucial for IFNs production to limit virus replication, particularly in the early stages of viral infection, long term overproduction of IFNs and cytokines can cause immunopathologic lung injury following acute IAV infection. [13][14][15][16][17] Thus, targeting RIG-I signaling to suppress RIG-I long-lasting hy- After 4 days, the number of plaques was then counted.…”
mentioning
confidence: 99%
“…There might be extensive cooperative and/or competitive interactions among different PRRs that support and regulate antiviral sensing and induction of innate immune responses. Our previous publication demonstrated that RIG-I overexpression in the lung improves survival of cigarette smoke-exposed mice during IAV infection [ 17 ]. This suggests that, although solitary PRR deficiency might be dispensable in innate response to IAV, overexpression of one major PRR is sufficient to restore the innate response to IAV infection in an immunosuppressed cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Gene-specific primers for mouse PRRs, cytokines, and the β -actin housekeeping genes were used. The primers' sequences were the same as in our earlier publication [ 17 ]. qRT-PCR was performed using 100 ng sample RNA and SYBR Green (Quanta Biosciences, Gaithersburg, MD) in a Bio-Rad CFX96™ Touch Real-Time PCR Detection System.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RIG-I is essential for IFN induction during RNA virus infections of non-pDC cell types, and mice that are deficient in RIG-I-like receptor signaling pathways are extremely susceptible to other RNA viruses [14][15][16]. Our previous work using RIG-I transgenic mice showed that RIG-I overexpression in mice protects against cigarette smoke enhanced susceptibility of these animals to influenza infection [17]. Although PRRs are important in innate cytokine response in vitro, the deletion of genes encoding PRRs other than RIG-I does not worsen survival during IAV infection in vivo.…”
Section: Introductionmentioning
confidence: 99%